2021
DOI: 10.1038/s41598-021-91317-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of phenotypic plasticity sheds light on the evolution and molecular underpinnings of locust phase polyphenism

Abstract: Locusts exhibit one of nature’s most spectacular examples of complex phenotypic plasticity, in which changes in density cause solitary and cryptic individuals to transform into gregarious and conspicuous locusts forming large migrating swarms. We investigated how these coordinated alternative phenotypes might have evolved by studying the Central American locust and three closely related non-swarming grasshoppers in a comparative framework. By experimentally isolating and crowding during nymphal development, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 102 publications
2
19
1
Order By: Relevance
“…S4: https://doi.org/10.6084/m9.figshare.20174255.v1). The previous studies showed that ebony, Mcm2, and Mcm7 were upregulated in response to crowded condition, and Duox, Mdr49 and Cyp6a14 were downregulated in response to crowded condition (i. e. upregulated in response to isolated condition) [14,33,34]. In this study, CI score of these genes showed high or low values (Figure 1).…”
Section: Gene Set Enrichment Analysissupporting
confidence: 56%
“…S4: https://doi.org/10.6084/m9.figshare.20174255.v1). The previous studies showed that ebony, Mcm2, and Mcm7 were upregulated in response to crowded condition, and Duox, Mdr49 and Cyp6a14 were downregulated in response to crowded condition (i. e. upregulated in response to isolated condition) [14,33,34]. In this study, CI score of these genes showed high or low values (Figure 1).…”
Section: Gene Set Enrichment Analysissupporting
confidence: 56%
“…Consequently, 66 pairs of transcriptome data were collected from the public databases ( Table 1 ). Full information about the dataset used in this study is provided in Table S2 [ 10 , 31 , 32 , 33 , 34 , 35 ]. These data comprised transcriptomes from seven insect species, including aphids and locusts.…”
Section: Resultsmentioning
confidence: 99%
“…CI scores were calculated based on the CI ratio table ( Table S4 ). The previous studies showed that ebony , Mcm2 , and Mcm7 were upregulated in response to crowded condition, and Duox , Mdr49 and Cyp6a14 were downregulated in response to crowded condition (i.e., upregulated in response to isolated condition) [ 14 , 33 , 34 ]. In this study, the CI score of these genes showed high or low values ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembled de novo unigenes were obtained, which were the encoding sequences. The redundancy was filtered using the Cd-hit-EST (Foquet et al, 2021). The Transrate (v1.0.3) was used to map reads to contigs and inspect the alignments (Marx et al, 2021).…”
Section: De Novo Assembly and Annotationmentioning
confidence: 99%